Sublethal Effects of Flonicamid on Life Table of Myzus persicae (Sulzer) - Baral , Sabitri; Thapa, Resham Bahadur; Jha, Ratna Kumar; Joshi, Samudra Lal; Aryal, Sunil (Journal of the Plant Protection Society, 2023)
The green peach aphid, Myzus persicae (Sulzer) (Aphididae: Hemiptera) is a cosmopolitan polyphagous pest of more than five hundred plant species belonging to at least forty different plant families including several economically important agricultural crops. The sublethal effect of LC25 concentration of flonicamid on M. persicae was assessed by using an age-stage two-sex life table approach for integrated management of this pest. A leaf-dip bioassay showed that flonicamid was very toxic to the adults of M. persicae at 48 h with the calculated LC25 concentration value of 0.0115 g a.i./L. The adults (parental generation) of M. persicae exposed to the LC25 concentration (sublethal dose) of flonicamid showed inhibitory effects on the life history traits across its generations such as reduction in adult longevity and fecundity of parental generation (F0); shortening the durations of fifth instar nymphs, adult female longevity, oviposition period, total longevity and fecundity of F1 & F2 generations. On the other hand, stimulatory effects were observed on the duration of first, second, third, and fourth instar nymphs; and pre-adults in F2 generation in the flonicamid-treated aphids. Consistently with the effects on individual traits, a higher mean generation time (T) and shorter intrinsic rate of increase (r), finite rate of increase (λ), and net reproductive rate (R0) of F2 generation were observed in the flonicamid treated aphids, although r, λ, R0, T, and gross reproductive rate (GRR) of F1 generation were not significantly affected. The findings revealed the exposure of parental adults of M. persicae to sublethal concentration of flonicamid could induce hormetic (both inhibitory and stimulatory) effects on their succeeding generations. This study is useful for assessing the overall effects of flonicamid on M. persicae. The hormetic effects should be considered when it used flonicamid in the integrated management of M. persicae in crop fields.